2015
DOI: 10.1016/j.jbiosc.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Culture characteristics of the atmospheric and room temperature plasma-mutated Spirulina platensis mutants in CO2 aeration culture system for biomass production

Abstract: For biomass production of Spirulina platensis as feedstock of fermentation, the culture characteristics of three typical mutants of 3-A10, 3-B2 and 4-B3 generated by atmospheric and room temperature plasmas (ARTP) mutagenesis were systematically studied by using CO2 aeration culture system and compared with the wild strain. The specific growth rate of wild strain in the pure air aeration culture system exhibited a 76.2% increase compared with static culture, while the specific growth rates of the 3-A10, 3-B2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…On the other hand, strain M5 showed the highest carotenoid content (2.63 µg/mgDW). These results were comparable with the findings of earlier studies that reported a ~ twofold increase in the total Chl of Spirulina platensis by applying ARTP [ 20 , 34 ]. In contrast, the chlorophyll content and fluorescence of Chlamydomonas reinhardtii were reported to decrease significantly after ARTP treatment [ 19 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, strain M5 showed the highest carotenoid content (2.63 µg/mgDW). These results were comparable with the findings of earlier studies that reported a ~ twofold increase in the total Chl of Spirulina platensis by applying ARTP [ 20 , 34 ]. In contrast, the chlorophyll content and fluorescence of Chlamydomonas reinhardtii were reported to decrease significantly after ARTP treatment [ 19 ].…”
Section: Resultssupporting
confidence: 92%
“…The change in the content of cell components has been previously confirmed by ARTP mutagenesis [ 12 , 20 ]. In the present work, the M8 strain showed low carbohydrate content but a significant pigment, protein and lipid accumulation.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In 2010, Wang et al first successfully implemented the helium ARTP mutagenesis system to obtain mutants of Streptomyces avermitilis with high productivity of avermectins. Subsequently, the ARTP has been successfully employed to improve or decrease the different properties of various bacteria, fungi and microalgae (Jiang et al 2017;Liu et al 2017;Tan et al 2015), including the metabolite, biochemical and enzyme activities (Guo et al 2011;Lu et al 2011;Xu et al 2012;Zong et al 2012).…”
Section: Screening and Verification Of The Mutantsmentioning
confidence: 99%
“…They play a key role in the global carbon/oxygen cycle ( Sánchez-Baracaldo et al., 2022 ) and are harnessed by diverse industries as sustainable feedstock for the production of high-value compounds ( Boutarfa et al., 2022 ; Santos-Merino et al., 2023 ). Moreover, they are considered ideal candidates for the development of next-generation biofuels and other biotechnologically relevant substances because of their potential for genetic manipulation and their ability to proliferate under diverse environmental conditions ( Tan et al., 2015 ; Patel et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%